Genome sequence and genetic diversity of European ash trees - Sollars, E; Harper, A; Kelly, L; Sambles, C; Ramirez-Gonzalez, R; Swarbreck, D; Kaithakottil, G; Cooper, E; Uauy, C; Havlickova, L; Worswick, G; Studholme, D; et al. (Nature Publishing Group, 2016)
Ash trees (genus Fraxinus, Oleaceae) are widespread throughout the Northern Hemisphere, but are being devastated in Europe by the fungus Hymenoscyphus fraxineus, causing ash dieback (ADB), and in North America by the Emerald Ash Borer (EAB), Agrilus planipennis1,2. We sequenced the genome of a low-heterozygosity Fraxinus excelsior tree from Britain annotating 38,852 protein-coding genes of which 25% appear ash specific when compared with ten other plant species’ genomes. Analyses of paralogous genes suggest a whole-genome duplication shared with olive (Olea europaea, Oleaceae). We resequenced 37 F. excelsior trees from Europe finding evidence for apparent long-term decline in effective population size. Using our reference sequence, we re-analysed association transcriptomic data3, yielding improved markers for reduced susceptibility to ADB. Surveys of these markers in British populations suggested that reduced ADB susceptibility may be more widespread in Great Britain than in Denmark. We also present evidence that susceptibility of trees to H. fraxineus is associated with their iridoid glycoside levels. This rapid, integrated, multidisciplinary research response to an emerging health threat in a non-model organism opens the way for mitigation of the epidemic.